Intense intermittent exercise provides weak stimulus for vascular endothelial growth factor secretion and capillary growth in skeletal muscle. Issue 2 (6th December 2012) - Hoier, B.; Passos, M.; Bangsbo, J.; Hellsten, Y.
<x xml:space="preserve">Abstract</x> The effect of acute intense intermittent exercise compared with moderate‐intensity exercise on angiogenic factors and the effect of 4 weeks of intense intermittent training on capillary growth were examined in nine healthy young men, preconditioned by moderate‐intensity endurance training. The intense training consisted of 24 bouts of 1 min cycling at an initial work rate of 316 ± 19 W (∼117% of pretraining maximal oxygen uptake), performed three times per week. Skeletal muscle biopsies and muscle microdialysates were otained from the vastus lateralis before, during and after acute exercise performed at either moderate or high intensity. Comparison of the response in angiogenic factors to acute moderate‐ versus high‐intensity exercise, performed prior to the intense training intervention, revealed that intense exercise resulted in a markedly lower (∼60%; P < 0.05) increase in interstitial vascular endothelial growth factor than did moderate‐intensity exercise. Muscle interstitial fluid obtained during moderate‐intensity exercise increased endothelial cell proliferation in vitro more than interstitial fluid obtained during intense exercise (sixfold versus 2.5‐fold, respectively; P < 0.05). The 4 weeks of high‐intensity training did not lead to an increased capillarization in the muscle but abolished the exercise‐induced increase in mRNA for several angiogenic factors, increased the protein levels of endothelial nitric oxide synthase, lowered the protein levels of thrombospondin‐1 in muscle but increased the interstitial protein levels of thrombospondin‐1. We conclude that intense intermittent exercise provides a weak stimulus for vascular endothelial growth factor secretion and endothelial cell proliferation and that intense intermittent training does not induce a sufficient angiogenic stimulus to induce capillary growth in muscle previously conditioned by moderate‐intensity exercise.